Family Economic Description In Fulfill Maternal Health during the Covid-19 Pandemic - Ferida Rahmawati; Emi Nurlaela; Arina Lutfiana (Sahmiyya, 2022)
Economic conditions and health are debates that are not easy to resolve in the early days of the COVID-19 pandemic. Families need income to meet their daily needs, including the need for the health of all family members, including maternal health. This study aims to describe the economic conditions during the COVID-19 pandemic in fulfilling maternal health. This research is a descriptive quantitative research. The population in this study were married women. Accidental sampling technique with a total of 40 respondents. The results showed that the age of respondents was more than 35 years as many as 53% of respondents. Respondents with the most places of residence in the city of Pekalongan as much as 45%. Work as educators as much as 52%. Families with 2 people who work in one house as much as 80%. Respondents who have a double job 20%. There are 20% of families who still have the responsibility to meet the needs of other families. As many as 61% of respondents experienced a change in income less than 25%. Respondents who determine the solution to create a business/other job in connection with changes in the family's economy are 42% of respondents. The basic needs during the COVID-19 pandemic were met in 78% of respondents. As many as 80% of respondents set aside income for health funds only 5-10%. Suggestions for further researchers to develop family economic research with different methods and more varied respondents.